Usnic acid biological activity: history, evaluation and usage - Alahmadi, Ahlam Abdulaziz (International Journal of Basic & Clinical Pharmacology, 2017)
Since Usnic acid (UA) was isolated from lichen metabolite in 1844, a lot of studies were conducted on it and now it became commercially available in the market. Its wide availability in different lichen species, being isolated easily, and high purity of the isolated product make it an excellent base for producing new pharmaceuticals. In this review the different usage of UA was summarized. It was utilized as an antioxidant, anti-proliferative, antimicrobial and antiprotozoal, larvicidal and insecticidal, antifungal, antiviral, algicidal, anti-inflammatory, pain-relieving and antipyretic agent. Many adverse effects were associated with using usnic acid, especially at high dose, including; hepatotoxicity, genotoxicity, allergenicity, side effects on the cardiovascular system and adipocytes of fatty tissue. This review aimed to throw the light on the updated biological activities, effectiveness and safety and usage of usnic acid during the last decade.